Coupled Thermal Field of the Rotor of Liquid Floated Gyroscope. (12th August 2015) - Zhengjun, Wang; Yiyong, Yang; Jianzhong, Yang
Abstract : Inertial navigation devices include star sensor, GPS, and gyroscope. Optical fiber and laser gyroscopes provide high accuracy, and their manufacturing costs are also high. Magnetic suspension rotor gyroscope improves the accuracy and reduces the production cost of the device because of the influence of thermodynamic coupling. Therefore, the precision of the gyroscope is reduced and drift rate is increased. In this study, the rotor of liquid floated gyroscope, particularly the dished rotor gyroscope, was placed under a thermal field, which improved the measurement accuracy of the gyroscope. A dynamic theory of the rotor of liquid floated gyroscope was proposed, and the thermal field of the rotor was simulated. The maximum stress was in x, 1.4; y, 8.43; min 97.23; and max 154.34. This stress occurred at the border of the dished rotor at a high-speed rotation. The secondary flow reached 5549 r/min, and the generated heat increased. Meanwhile, the high-speed rotation of the rotor was volatile, and the dished rotor movement was unstable. Thus, nanomaterials must be added to reduce the thermal coupling fluctuations in the dished rotor and improve the accuracy of the measurement error and drift rate.